The Influence Of Proactive Behavior And Psychological Empowerment On Innovative Work Behavior: Moderating Role Of Job Characteristic - Gultom, Lasmaida; Suroso, Gito; Gasjirin, Juliana (Riviera Publishing, 2022)
This study aims to analyze the influence between variables such as innovative work behavior, psychological empowerment, proactive behavior and work characteristics of Generation Y employees of Indonesia Financial Services Authority (IFSA). The endogenous variables in this study consisted of proactive behavior and psychological empowerment, the exogenous variable was innovative work behavior, and the job characteristic was moderator variable. The main hypothesis of this study is a theoretical model of the effects of proactive behavior and psychological empowerment on innovative work behavior modulated by job characteristic, according to empirical data on IFSA Generation Y workers. Data collection techniques were performed by measuring self-report using the proactive behavior scale, the psychological empowerment scale, the innovative work behavior scale, and the job characteristic model. Structural equation model (SEM) data analysis using LISREL analysis. The sampling procedure was performed with a simple random sample of 279 respondents. The results show that proactive behavior and psychological empowerment have a significant positive effect on innovative work behavior moderated by job characteristic, with an RMSEA coefficient of 0.012 and a GFI coefficient of 0.99, the hypothesis was accepted